Step 1

In first step, simplify the equation to form a more specific form where variables are on one side and constant values on the other side of equality as.

\(\displaystyle{\frac{{{7}}}{{{x}}}}+{x}={\frac{{{88}}}{{{x}}}}\)

multiply by x on both sides of equation;

\(\displaystyle{\left({\frac{{{7}}}{{{x}}}}+{x}\right)}{x}={\left({\frac{{{88}}}{{{x}}}}\right)}{x}\)

\(\displaystyle{7}+{x}^{{{2}}}={88}\)

\(\displaystyle{x}^{{{2}}}={88}-{7}\)

\(\displaystyle{x}^{{{2}}}={81}\)

Step 2

Now solve for x, to get the desired values as.

\(\displaystyle{x}^{{{2}}}={81}\)

\(\displaystyle{x}=\pm\sqrt{{{81}}}\)

\(\displaystyle{x}=\pm{9}\)

x=9, -9

In first step, simplify the equation to form a more specific form where variables are on one side and constant values on the other side of equality as.

\(\displaystyle{\frac{{{7}}}{{{x}}}}+{x}={\frac{{{88}}}{{{x}}}}\)

multiply by x on both sides of equation;

\(\displaystyle{\left({\frac{{{7}}}{{{x}}}}+{x}\right)}{x}={\left({\frac{{{88}}}{{{x}}}}\right)}{x}\)

\(\displaystyle{7}+{x}^{{{2}}}={88}\)

\(\displaystyle{x}^{{{2}}}={88}-{7}\)

\(\displaystyle{x}^{{{2}}}={81}\)

Step 2

Now solve for x, to get the desired values as.

\(\displaystyle{x}^{{{2}}}={81}\)

\(\displaystyle{x}=\pm\sqrt{{{81}}}\)

\(\displaystyle{x}=\pm{9}\)

x=9, -9